SOSIALISASI PEMBUATAN PUPUK ORGANIK BERBAHAN DASAR KOTORAN SAPI DAN LIMBAH ORGANIK DI DESA LEMING KECAMATAN TERARA KABUPATEN LOMBOK TIMUR - Rohyani, Immy Suci; Wandika; Andhika, Bagas Dwi; Hassanuddin B, M. Sultan; Pratiwi, Eka; Rahmasari, Synthia Nur; Aulia, Mulyani Safitri; Sumiyati, Sri; Rasidi, Muhammad; Annisa; Putri, Sasi Fhatmayani (Universitas Mataram, 2024)
Leming Village is a village located in the Terara District, East Lombok Regency, which is known for its large number of cattle breeders. The cow manure produced by these livestock has become an important issue that needs to be addressed in Leming Village due to the increasing amount of waste produced. Livestock waste, such as cow manure and other organic materials such as leaves, rice straw, and corn stalks, are the main sources of organic fertilizer. This organic fertilizer is useful in building soil fertility, especially if its use is done continuously over a long period of time. This activity aims to increase the understanding and skills of the community in managing cattle manure and organic waste into compost that is useful for agriculture and environmental cleanliness. This activity is carried out through socialization activities regarding the organic compost program from cattle manure and organic waste, implementation of activities in the form of counseling and compost making techniques from cattle manure and organic waste, as well as additional materials that will be used to accelerate compost making, then conducting evaluation and monitoring as well as community assistance. The results of the compost making process showed that temperature and pH checks were carried out twice, where the checks were carried out in the first and second weeks after the compost was made. The temperature check results in the first week showed that the temperature of the compost was 35Â°C with a pH of 5.5 and in the second week showed a value of 27Â°C and pH 7. With this activity, the community can process cattle manure into organic fertilizer, reduce the cost of purchasing chemical fertilizers, and maintain soil fertility better than the use of chemical fertilizers that can reduce fertility.